Impact of music on anxiety and pain control during extracorporeal shockwave lithotripsy: A protocol for systematic review and meta-analysis. Issue 4 (29th January 2021) - Wang, Zhenghao; Feng, Dechao; Wei, Wuran
Abstract: Background: The present evidence is insufficient for evaluating the impact of exclusive music therapy on anxiety and pain control in extracorporeal shock wave lithotripsy (ESWL). Methods: A systematic review and meta-analysis was conducted to explore the efficacy of music therapy in reducing pain and anxiety in patients undergoing ESWL. PubMed, Web of Science, Embase, EBSCO, and Cochrane library databases (updated March 2020) were searched for randomized controlled trials assessing music therapy in reducing pain and anxiety in patients undergoing ESWL. The search strategy and study selection process were managed according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis statement. Results: Five randomized controlled trials were included in the meta-analysis. Overall, music intervention groups experienced significant reductions in pain (risk ratios = –1.20, 95% confidence intervals = –1.95 to –0.45, P = .002) and anxiety (risk ratios = –3.31, 95% confidence intervals = –4.97 to –1.84, P < .0001) compared with control groups during ESWL. Music therapy gave patient more satisfaction with the treatment and a willingness to repeat the therapy was reported. However, there was no significant difference in the stone clearance rate. Conclusions: Listening to music can reduce patient's pain and anxiety significantly with increased therapy satisfaction and willingness to repeat.